Pengaruh Penerapan Metode Storytelling Berbasis SAVI untuk Meningkatkan Daya Ingat Siswa Mata Pelajaran Akidah Akhlak di MA Salafiyah Merakurak - Nikmatul Asiyah; Sani Latifatul Khilmina (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This research aims to investigate the implementation of the storytelling method based on SAVI in Akidah Akhlak learning at MA Salafiyah Merakurak. This study employs a quantitative approach with a one-group pretest-posttest design, involving class X students as subjects. It utilizesdata collection techniques that include pretests, posttests, observations, and documentation. Data analysis was conducted using descriptive statistics and a dependent t-test to measure the effect of the treatment on students' memory retention. The research findings indicate that the application of the SAVI-based storytelling method successfully enhanced students' engagement and memory retention in Akidah Akhlak learning. Students demonstrated greater focus, enthusiasm, and active involvement during the learning process. The integration of various learning modalities (somatic, auditory, visual, and intellectual) helped students comprehend abstract akidah concepts more meaningfully. The average memory retention score significantly improved from the "fair" to the "excellent" category following the treatment. Statistical testing revealed a significant difference between pretest and posttest scores, confirming the positive effect of the SAVI-based storytelling method on improving memory retention. The paired sample t-test results showed a Sig (2-tailed) value of 0.000 < 0.05, thus rejecting H0 and accepting Ha, indicating that the SAVI-based storytelling method significantly influences the enhancement of students' memory retention. This method can serve as an innovative and relevant alternative learning strategy in Islamic Religious Education.   Keywords: SAVI-based storytelling, Akidah Akhlak, Student’s Memory, Improvement in Learning Outcomes, Religious Education Innovation.